MohjaKahf’s Poetry: Promoting Intercultural Understanding Between Muslim and Non- Muslim Americans - Abdulkareem Khalid, Najwa (Opción, 2019)
MohjaKahf (b. 1967) is a Syrian- American poet whose poetry is characterized by its cultural opposition to any American stereotyping of Muslims and Islam in gen- eral and Arab - Muslim Americans in specific. The American mainstream culture has its own misconceptions about Arab-Muslims which result in a wave of Islamo- phobia and anti-Arab hate throughforming a stereotype of the Arab-Muslim people as ignorant terrorists. This paper examines the struggle between Kahf’s Islamic concepts and the concepts of the American culture in which she lives.Being a hy- brid Arab-Muslim American, Kahf is fully aware of both cultures and understands both languages which qualify her to play the role of a compromiser to bring the opponents into terms. The paper affirms that Kahf, through celebrating her Islamic identity, undertakes the task of a mediator between Islamic cultural customs and the modern American culture.